2020
DOI: 10.1136/jramc-2019-001282
|View full text |Cite
|
Sign up to set email alerts
|

Female UK Army Service personnel are at greater risk of work-related morbidity on return to duty postpartum

Abstract: IntroductionThe 2016 Interim Report on the Health Risks to Women in Ground Close Combat Roles highlighted an increased risk of skeletal injury and significant physiological changes, including increased ligament laxity and decreased bone mineral content, during the postpartum period. The report called for further research and a re-evaluation of postpartum policy to optimise the return of female Service personnel to arduous employment. The purpose of this study was to determine whether returning to duty is at gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The number of working days lost due to illness and injury per week was twofold higher postpartum than prepregnancy (14). Postnatal depression and gynecological disorders were the most common causes of workdays lost due to illness (14). Similarly, several studies have shown that U.S. military servicewomen are returning to work unprepared for the demands of their role because of reduced physical fitness compared with prepregnancy, and with symptoms of depression and anxiety (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of working days lost due to illness and injury per week was twofold higher postpartum than prepregnancy (14). Postnatal depression and gynecological disorders were the most common causes of workdays lost due to illness (14). Similarly, several studies have shown that U.S. military servicewomen are returning to work unprepared for the demands of their role because of reduced physical fitness compared with prepregnancy, and with symptoms of depression and anxiety (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…As of October 1, 2020, 99% of servicewomen who went on maternity leave returned to work within 27 to 40 wk after giving birth (3). Recent data suggest that postpartum UK servicewomen are at greater risk of illness and injury in the year after giving birth compared with prepregnancy (14). The number of working days lost due to illness and injury per week was twofold higher postpartum than prepregnancy (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UK servicewomen can return to physically and psychologically demanding roles after 2 weeks of compulsory maternity leave. Previous data show that British Army servicewomen return to work within the first year after childbirth and are at greater risk of illness and injury during this time than before pregnancy [ 31 ]. US military servicewomen do not achieve prepregnancy fitness levels at 6 months following childbirth [ 32 - 34 ], and servicewomen commonly experience symptoms of fatigue, depression, and anxiety upon returning to work [ 33 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Responding to a gender data gap in defence that is also evident in wider society, as described in the editorial by Greeves et al ,2 this supplement has been curated to evaluate sex differences in musculoskeletal injuries in training3 and the trained strength,4 the biomechanics of load carriage,5 the cognitive responses to load carriage,6 and the prevalence of, and risk factors for, mental ill-health 7. We also discuss unique challenges for women, including the prevalence of injury and illness on return to work following childbirth,8 and both the prevalence of hormonal contraceptive use9 and influence of hormonal contraceptive use on bone metabolism 10. Defence quipment and support have worked with the Defence Science and Technology Laboratories and the Royal Centre for Defence Medicine to define the optimal sizes of body armour plates for the female soldier using CT scans and the most recent anthropometric survey 11.…”
mentioning
confidence: 99%